PENERAPAN ALGORITMA K-MEANS CLUSTERING SEBAGAI STRATEGI PROMOSI PENERIMAAN MAHASISWA BARU PADA UNIVERSITAS HASYIM ASY’ARI JOMBANG - Mahmudi, Imam; Dwi Indriyanti, Aries; Lazulfa, Indana (Inovate, 2020)
Admission of new students at the Hasyim Asy'ari University in Jombang is held every year. To more of the newstudents, admissions Committee conducted several promotions as very important early activities such as: online,banners, brochures, school events, and orally with student roles and Alumni. The number of competition infinding new student applicants, requiring the University of Hasyim Asy'ari to conduct analysis of several waysof promotion that have been done so that the promotion strategy can be seen which is more precise and effective.This research will conduct grouping/clustering of districts or cities based on certain attributes in a Web-basedapplication. The method used in this study is a K-means clustering algorithm that can group student data intomultiple clusters based on similar attribute agreements. The attributes used are hometown, online, oral,banners/billboards, brochures and events. At this Peletitian generate a total of 5 clusters (k = 5) with the firstcluster 20 hometown with the most effective promotional media online and oral, the second cluster of 31 Origincities with the most effective promotional media oral and online, the third cluster of 4 cities originating withmedia The most effective promotion of events and banners, the fourth cluster of 15 hometown with the mosteffective promotional media brochures and oral, the fifth cluster 2 hometown with the most effective promotionalmedia oral and event. The results of this study were used as a recommendation to determine a promotionalstrategy based on the promotional media of each cluster formed.Keywords: Promotion strategy, Admission of New Students, K-means Algorithm, Clustering